A nanozyme tag enabled chemiluminescence imaging immunoassay for multiplexed cytokine monitoring. Issue 98 (21st November 2018) - Zhong, Yihong; Tang, Xiao; Li, Juan; Lan, Qingchun; Min, Lingfeng; Ren, Chuanli; Hu, Xiaoya; Torrente-Rodríguez, Rebeca M.; Gao, Wei; Yang, Zhanjun
Abstract : We propose a new concept of a chemiluminescence imaging nanozyme immunoassay (CINIA), in which nanozymes are exploited as catalytic tags for simultaneous and high-throughput multiplex detection of cytokines. Abstract : We report a new concept of a chemiluminescence imaging nanozyme immunoassay (CINIA), in which nanozymes are exploited as catalytic tags for simultaneous multiplex detection of cytokines. The CINIA provides a novel and universal nanozyme-labeled multiplex immunoassay strategy for high-throughput detection of relevant biomarkers and further disease diagnosis.